Testy inteligencji w ocenie i rekrutacji pracowników IT - Grobelny, Jarosław (Politechnika Łódzka, 2015)
In case of deficiency of IT staff, their effective assessment and recruitment is one of the most important tasks for HR departments. The popular practice of assessing and taking into account only technical competence (eg. knowledge of a programming language) when recruiting is compared with the proposal to use intelligence tests. The general level of intelligence is one of the most tested and proven predictors of professional efficiency. The results of studies proving that for IT staff it is also worth to use intelligence tests in the assessment and recruiting are presented, simultaneously indicating that the general factor of intelligence is more effective in estimating the employee efficiency, than the single, specific cognitive abilities.
Keywords: GMAT; zarządzanie oparte na dowodach; testy inteligencji; HR; rekrutacja; dobór personelu